Ultrasonic Assisted Enhancement in Natural Dye Extraction from Eucalyptus for Process Optimization - Faisal Rehman; Tayyab Naveed; Rehana Ilyas; Noor Sanbhal; Muhammad Awais; Wang Wei (Journal of Natural Fibers)
The research focuses on the effective extraction of natural dye from Eucalyptus (Eucalyptus globulus L.) leaves and process optimization of coloration using tencel fabrics. Eucalyptus leaves were extracted using ultrasonic-assisted extraction and applied to tencel fabrics using exhaust dyeing method. The tencel fabric samples were dyed using pre-mordanting, simultaneous-mordanting, and post-mordanting techniques without and with mordants using different concentrations. The dye extraction and dyeing process were investigated at different temperatures and time durations to achieve an optimized process. The dyed samples were examined for color strength (K/S) and CIEL*a*b values by using Data Color spectrophotometer. Additionally, the dyed samples were tested for qualitative and quantitative antibacterial activity using standard protocols. The results revealed that ultrasonic extraction was efficient and effective for the dyeing of tencel using eucalyptus dye at 60°C with a time span of 30 min. The pre-mordanting method demonstrated better results in terms of shade depth and colorfastness. Tencel fabric dyed in the presence of ferrous sulfate mordant revealed superior dyeing results while potassium dichromate showed poor results. All the samples possessed good antibacterial and good fastness properties. Thus, tencel fabrics dyed with eucalyptus dye through ultrasonic at low temperatures and short time could be valuable for textile industry.